The impact of exposure to scientific research and inclusive mentoring style on medical undergraduates’ perceptions of critical thinking, communication, and passion - Kecheng Zhou; Chunhua Cao; Xiao Liu; Mengqi Sun; Zhihan Wu; Weiqin Zheng; Cheng Peng (Medical Education Online)
There is a growing trend to integrate scientific research training into undergraduate medical education, and mentoring styles are believed to help develop students’ research capabilities. Critical thinking, attitude toward communication skills, and academic passion are important factors in enhancing students’ research capabilities. This study aimed to explore the impact of exposure to scientific research and mentoring styles on medical undergraduates’ critical thinking, attitude toward communication skills, and academic passion. This study surveyed 366 medical students from Central South China, assessing students’ research involvement, mentoring style, self-perceived items of critical thinking, attitude toward communication skills, harmonious academic passion, and obsessive academic passion. Structural equation modeling (SEM) was used to model the structural relationships between the exposure to research and the self-perceived latent factors. SEM results showed that the model fit was acceptable (CFI = 0.903, RMSEA = 0.070, and SRMR = 0.060) based on the cutoff criteria used in empirical research. SEM analysis revealed that exposure to research significantly influenced critical thinking (β = 0.139, p < .01) and communication attitude (β = 0.258, p < .001) but did not affect academic passion. An inclusive mentoring style significantly enhanced critical thinking (β = 0.472, p < .001), communication attitude (β = 0.423, p < .001), and harmonious academic passion (β = 0.377, p < .001). Inclusive mentoring plays a crucial role in enhancing medical students’ critical thinking, communication skills, and harmonious academic passion. Medical institutions should focus on strengthening mentoring programs to better support these outcomes.